Efektivitas Pemberian Egg Stimulant terhadap Produktivitas Larva Ikan Nila Nirwana di Ernawati Farm Galunggung (EFG) Tasikmalaya - Nurjanah, Lilis; Malahayati, Shadiqa; AS, Agus Putra; Pangentasari, Dwinda (Jurnal Akuakultur Sungai dan Danau, 2025)
Low fry quality and the lack of continuous fry availability are major constraints in Nile tilapia cultivation. One of the primary factors contributing to poor fry quality is the inadequate nutritional quality of broodstock feed. Egg stimulant is a feed additive containing multivitamins and minerals that can enhance egg production, improve egg quality, extend the spawning phase, and accelerate gonadal maturation. However, its effectiveness depends on species, broodstock age, and environmental conditions. This study aimed to evaluate the effectiveness of egg stimulant supplementation on larval productivity of Nirwana strain Nile tilapia at Ernawati Farm Galunggung (EFG) through broodstock feeding. Five treatments with three replications were applied, consisting of egg stimulant dosages of 0.25 g/kg, 0.33 g/kg, 0.5 g/kg, 1 g/kg, and a control. Observed parameters included the number of larvae produced per harvest and the daily growth rate of both female and male broodstock during the spawning period. Supplementation of egg stimulant to broodstock feed significantly increased the number of larvae produced per cycle, with the best performance observed in treatment P IV (1 g/kg). However, feed supplementation with egg stimulant did not result in a significant difference in broodstock body weight growth for either sex. Nevertheless, numerical improvements in weight gain were observed, indicating that the supplementation did not inhibit growth and supported the physiological performance of the broodstock